Bioactive carbazole alkaloids from Clausena wallichii roots - Wisanu Maneerat (2018)
Four new carbazole alkaloids, clausenawallines C-F (1-4), along with 18 known compounds (5-22) were isolated from the roots of Clausena wallichii. Compounds 3, 9, and 22 exhibited significant antibacterial activity against methicillin-resistant Staphylococcus aureus SK1 (MRSA SK1) and Staph. aureus TISTR 1466 with MIC values in the range 4-16 μg/mL, whereas compound 4 showed the highest cytotoxicity against oral cavity cancer (KB) and small-cell lung cancer (NCI-H187) with IC50 values of 10.2 and 4.5 μM, respectively. © 2012 The American Chemical Society and American Society of Pharmacognosy.